Motivasi dan Budaya Organisasi: Dampaknya terhadap Kinerja Pegawai dengan Mediasi Disiplin Kerja - Nursaid Nursaid; Nurul Qomariah; Yoangga Muhammad Jakfar Sidik (BUDGETING : Journal of Business, Management and Accounting, 2023)
This paper aims to analyze the impact of motivation and organizational culture on work discipline and employee performance at the Office of Cooperatives and Micro Enterprises, Jember Regency. This study used a population of all employees of the Office of Cooperatives and Micro Enterprises of Jember Regency with a total of 55 employees. The total population of 55 employees is all used as a sample in the study using the saturated sample technique. Descriptive analysis to analyze the description of the respondents related to gender, age, and years of service. Test the validity and reliability test to test the questionnaire in this study. Structural Equation Modeling (SEM) analysis with WarpPLS 5.0 to test the research hypothesis. The results in this study indicate that motivation and organizational culture have an impact on work discipline. In addition, work motivation, organizational culture and work discipline have an impact on employee performance. The conclusion from this research is that the Department of Cooperatives and Micro Enterprises of Kab. Jember is obliged to increase motivation, culture and work discipline in order to improve the performance of its employees. Keywords: Organizational Culture, Work Discipline, Employee Performance, Work Motivation